Analisis Miskonsepsi Siswa Pada Materi Teori Kinetik Gas Kelas Xl SMAN 8 Yogyakarta - Mikelis Ovani Salus; Winarti (Edusainstika, 2025)
This study is a descriptive quantitative research that aims to describe the percentage of students who understand, misunderstand (experience misconceptions), and do not understand the concepts in the topic of the kinetic theory of gases using a three-tier test. In addition, this study also aims to describe the factors that cause student misconceptions. A total of 17 students were clinically observed to obtain data regarding the causes of misconceptions. The results of the study show that the highest rate of student misconceptions occurred in the sub-concept of the gas law equation, amounting to 47.05%, while 41.17% of students understood the concept, and the remaining 11.76% did not understand the concept.The factors contributing to student misconceptions include a teacher-centered learning approach in high-performing schools, where teachers tend to use lecture-based or fast-paced instruction strategies to meet curriculum targets and academic competitions. This limits opportunities for students to independently construct their understanding or engage in exploratory discussions. Moreover, the absence of consistent learning resources results in teachers becoming the dominant and often sole source of information┬áfor┬ástudents.